Photographic representations of Brussels at the turn of the 19th and 20th centuries: from documentation to artistic expression - Danielle Leenaerts (Brussels Studies)
The period between 1880 and 1900 was a determining moment for urbanism in Brussels as well as for the recognition of photography as an art form. The policy regarding major work sites during the reign of Léopold II was essential in the definition of the Brussels urban identity. At the same time, the status of photographers was redefined. The pioneering photographers from the previous period were followed by a generation of amateurs – in the noble sense of the term – who defended the autonomy of what they considered to be an art form in itself. As part of a fundamental international movement referred to as “Pictorialism” which emerged in the mid 1880s, they modelled their work after painting and favoured timeless subjects. The relationship between the city and its photographic representation was modified, and was seen more as a landscape, including a periurban one. The personal points of view of the urban landscape therefore multiplied, encouraged by the artistic photography circles united within the Belgian Photography Association.